La cinéphilie chrétienne : Amédée Ayfre (1922-1964), sulpicien et critique de cinéma - Philippe Rocher (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
In the middle Twentieth century, Amédée Ayfre, French priest of the Society of saint Sulpice and Christian cinema enthusiast, defended esthetic and realism cinema against the religious cinema of « Catholic cinema ». For him, realist Cinema is the Christian revelation instrument of fellow man. Brusquely to die, he can’t proposed any more his first “Jalons pour une théologie de l’image”.